PENGARUH KOMITMEN ORGANISASI TERHADAP KINERJA YANG DIMEDIASI OLEH ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) STUDI PADA PENDAMPING DESA KABUPATEN WAKATOBI - Sutrino, Anas; Nirwati, Nurwati; Adam, Laode Bahana (JPEP (Jurnal Progres Ekonomi Pembangunan), 2019)
This study aims to examine and explain the effect of organizational commitment on performance mediated by the Organizational Citizenship Behavior (OCB) study in the Village Facilitator of Wakatobi Regency. The approach of this study is a survey with an explanatory research design. Data collection is done using survey methods through questionnaires and interviews. The population of this study was 43 people of the Wakatobi Regency village companion. Because the population in this study is relatively small, all the populations in the study were made as respondents. The analytical equipment used is Partial Least Square (PLS).The results showed that organizational commitment had a positive and significant effect on performance, a positive and not significant effect on OCB; OCB has a negative and not significant effect on performance; OCB cannot mediate between organizational commitment and the performance of village facilitators.Â Keywords: Organizational Commitment, Organizational Citizenship Behavior (OCB), and Performance